Comparing the effectiveness of word cards and list learning with Japanese learners of English - Magda L. Kitano; Katsuhiro Chiba (Vocabulary Learning and Instruction)
This study investigated the recall of words learned through two deliberate learning techniques, word cards and list learning. While the literature points to word cards as being more effective, Japanese learners of English are seen to prefer list learning, which may indicate unique learning styles stemming from a non-alphabetic L1. To test the efficiency of the two techniques for Japanese learners, 25 university students of varying English proficiency were divided into four groups. Following the within-subject design, all groups were subjected to both treatments. Twenty low-frequency English words were learned within a 20-min period using one method, and then 20 more words were similarly learned with the other method. Subjects were tested immediately after the treatments, after a 20-min distraction period, and after an interval of 2 weeks. Results from all three testing stages indicated that list learning was more effective than word cards for these students.